Protective effect of zinc gluconate on intestinal mucosal barrier injury in antibiotics and LPS-induced mice - Wang, Yongcai; Xiao, Juan; Wei, Sumei; Su, Ying; Yang, Xia; Su, Shiqi; Lan, Liancheng; Chen, Xiuqi; Huang, Ting; Shan, Qingwen (Frontiers in Microbiology, 2024)
The aim of the study is to investigate the function and mechanism of Zinc Gluconate (ZG) on intestinal mucosal barrier damage in antibiotics and Lipopolysaccharide (LPS)-induced mice.We established a composite mouse model by inducing intestinal mucosal barrier damage using antibiotics and LPS. The animals were divided into five groups:Control (normal and model) and experimental (low, medium, and high-dose ZG treatments). We evaluated the intestinal mucosal barrier using various methods, including monitoring body weight and fecal changes, assessing pathological damage and ultrastructure of the mouse ileum, analyzing expression levels of tight junction (TJ)-related proteins and genes, confirming the TLR4/NF-κB signaling pathway, and examining the structure of the intestinal flora.: In mice, the dual induction of antibiotics and LPS led to weight loss, fecal abnormalities, disruption of ileocecal mucosal structure, increased intestinal barrier permeability, and disorganization of the microbiota structure. ZG restored body weight, alleviated diarrheal symptoms and pathological damage, and maintained the structural integrity of intestinal epithelial cells (IECs). Additionally, ZG reduced intestinal mucosal permeability by upregulating TJ-associated proteins (ZO-1, Occludin, Claudin-1, and JAM-A) and downregulating MLCK, thereby repairing intestinal mucosal barrier damage induced by dual induction of antibiotics and LPS. Moreover, ZG suppressed the TLR4/NF-κB signaling pathway, demonstrating anti-inflammatory properties and preserving barrier integrity. Furthermore, ZG restored gut microbiota diversity and richness, evidenced by increased Shannon and Observed features indices, and decreased Simpson's index. ZG also modulated the relative abundance of beneficial human gut bacteria (Bacteroidetes, Firmicutes, Verrucomicrobia, Parabacteroides, Lactobacillus, and Akkermansia) and harmful bacteria (Proteobacteria and Enterobacter), repairing the damage induced by dual administration of antibiotics and LPS. Conclusion: ZG attenuates the dual induction of antibiotics and LPS-induced intestinal barrier damage and also protects the intestinal barrier function in mice.